Feline microRNA transcriptome in whole blood in 6 healthy cats and in 6 cats with preclinical hypertrophic cardiomyopathy - Hanås, Sofia; Lorent, Julie; Ohlsson, Åsa (Swedish University of Agricultural Sciences, 2022)
Aim to characterize differentially expressed miRNAS between healthy Norwegian Forest cats and healthy Domestic Shorthair cats, and to compare with cats with hypertropic cardiomyopathy (HCM)
Six neutered healthy cats, three male domestic cats (DOM) and one male and two female Norwegian Forest (NF) cats were included. Each healthy cat was matched (breed, sex, age, body-weight and body condition score) with a cat with HCM.
The dataset includes the miRDeep2 report, rawcounts miRNAs, differentially expressed miRNAs for contrasts compared using DESeq2, human and feline target genes producing messenger RNA (mRNA) and gene ontology analysis (GO) for these 12 cats.

Whole blood was collected in PAXgene blood RNA System frozen and stored in -20 °C until date of RNA-extraction for a median storage time of 177 days. Total RNA was extracted. Samples with an RNA integrity number (RIN)-value of 7.7 or higher were included in the study. Libraries were prepared and quantified and normalized prior sequencing. Paired-end sequencing data was generated. Bioformatic data processing and count genertion of known and novel miRNAs in cats were identified using miRDeep2. Mature miRNA and hairpin sequences were downloaded from miRBase with human as main reference, an mouse and dog assigned as close relatives. Main reference miRNAs identified in the dataset were classified as predicted known miRNAs, and miRNAs previously not described in the main reference were classified as novel miRNAs by miRDeep2. Only novel miRNAs with a miRDeep2 score of >5.0 was included in the count-file generated for subsequent differently expressed (DE)-analyses. Identification of DE miRNAs were performed in DESeq2.
Number of variables 6: breed, age, sex, body-weight, body condition score, healthy or hypertrophic cardiomyopathy.
The compiled files gives an overview of the data set.
Compiled Excel file “miRDeep2_counts_DEsignmiRNAcontrasts_compiled” is a compiled file with the miRDeep2 report, raw counts of miRNAs and the differentially expressed miRNAs found in the dataset. The following nine csv-files are named miR_ and the name of the file in the compiled Excel file.
Compiled Excel file “Target_HumanGOmiRNA_Feline_GOmiRNA_compiled” is a compiled file with the human and feline target genes producing messenger RNA for the differentially expressed miRNAs found in the dataset, gene ontology analysis of these miRNAS both for human and feline genes. The following nineteen csv-files are named Target_ and the name of the file in the compiled Excel file.

Mål att karaktärisera differentially expressed miRNAs mellan friska Norska skogkatter och friska huskatter, samt jämföra med katter med hypertrofisk kardiomyopati (HCM).
Sex kastrerade friska katter, tre huskatter (DOM) -hanar och en han- och två norska skogkatter (NF)-honkatter inkluderades. Varje frisk katt matchades (ras, kön, ålder, kroppsvikt och body condition score) med en katt med HCM.
Datasetet innehåller miRDeep2 rapporten, counts för miRNAs, differentially expressed miRNAs för de kontraster som jämförts i DESeq2, human och felina target gener som producerar messenger RNA (mRNA) och gene ontologi analys (GO) för dessa 12 katter.

Helblod samlades i PAXgene blod RNA System infryst och lagrat i -20 °C fram till datumet för RNA-extraktion med en median lagringstid på 177 dagar. Total RNA extraherades. Prover med ett RNA-integritetsnummer (RIN)-värde på 7,7 eller högre inkluderades i studien. Bibliotek förbereddes och kvantifierades och normaliserades före sekvensering. Parade sekvensdata genererades. Bioformatisk databearbetning och räkningsgenerering av kända och nya miRNA hos katter identifierades med hjälp av miRDeep2. Mogna miRNA- och prekursorer laddades ner från miRBase med människa som huvudreferens, en mus och hund tilldelas som nära släktingar. Huvudreferens miRNA som identifierats i datamängden klassificerades som förutsagda kända miRNA, och miRNA som tidigare inte beskrivits i huvudreferensen klassificerades som nya miRNA av miRDeep2. Endast nya miRNA med en miRDeep2-score på >5,0 inkluderades i räkningsfilen som genererades för efterföljande olika uttryckta (DE)-analyser. Identifiering av DE miRNA utfördes i DESeq2.
Antal variabler 6: breed, age, sex, body-weight, body condition score, healthy or hypertrophic cardiomyopathy.

Se engelsk beskrivning eller ReadMeDescription.txt för mer information om de olika ingående datafilerna.
Katt mikroRNA transkriptom i helblod hos 6 friska katter och hos 6 katter med preklinisk hypertrofisk kardiomyopati
Keywords: Norwegian Forest cat; Norsk skogkatt; breed; ras; microRNA; mikroRNA; hypertrophic cardiomyopathy; hypertrofisk kardiomyopati; Domestic cat; huskatt; Bioinformatics (Computational Biology); Bioinformatik (beräkningsbiologi); Genetics and Genomics; Genetik och genomik; Basic Medicine; Medicinska och farmaceutiska grundvetenskaper; Medical Genetics and Genomics; Medicinsk genetik och genomik; Veterinary Science; Veterinärmedicin